Isotopic analysis of Cu in blood serum by multi-collector ICP-mass spectrometry: a new approach for the diagnosis and prognosis of liver cirrhosis?1. Issue 3 (11th March 2015) - Costas-Rodríguez, Marta; Anoshkina, Yulia; Lauwens, Sara; Van Vlierberghe, Hans; Delanghe, Joris; Vanhaecke, Frank
<x xml:space="preserve">Abstract</x> The isotopic composition of blood serum Cu has been investigated as a potential parameter for the diagnosis and prognosis of liver cirrhosis.